Contemporary monologues for women / The good audition guides (Good audition guides., 2014)
50 monologues by some of the greatest writers working today, each with a summary of the vital information you need to place the piece in context and perform it to the best of your ability. In this volume of the Good Audition Guides, you'll find fifty fantastic speeches for women, all written since the year 2000, by some of our most exciting dramatic voices. Playwrights featured in Contemporary Monologues for Women include Mike Bartlett, Alexi Kaye Campbell, Caryl Churchill, Helen Edmundson, debbie tucker green, Ella Hickson, Lucy Kirkwood, Rona Munro, Joanna Murray-Smith and Enda Walsh, and the plays themselves were premiered at the very best theatres across the UK including the National Theatre, the Royal Shakespeare Company, the Bush, Soho and Hampstead Theatres, Manchester Royal Exchange, the Traverse in Edinburgh, the Abbey in Dublin, and many on the stages of the Royal Court. Drawing on her experience as an actor, director and teacher at several leading drama schools, Trilby James prefaces each speech with a thorough introduction including the vital information you need to place the piece in context (the who, what, when, where and why) and suggestions about how to perform the scene to its maximum effect (including the character's objectives and keywords). Contemporary Monologues for Women also features an introduction on the whole process of selecting and preparing your speech, and approaching the audition itself. The result is the most comprehensive and useful contemporary monologue book now available.